Allocation Reductions in Inconsistent Decision Tables Based on Dominance Relations - Wen-Sheng Du; Bao-Qing Hu (Fuzzy Information and Engineering, 2015)
In recent years, many methods have been proposed in order to deal with inconsistent information systems based on indiscernibility relations in rough set theory. However, a little attention has been paid to inconsistent ordered decision tables. In this paper, the concept of allocation reductions is proposed in inconsistent ordered decision tables. And an approach to computing this kind of reductions is then presented by introducing the discernibility matrix and discernibility function. Moreover, the relationship is investigated between the allocation reduction and the ≥-upper (≤-lower) approximate distribution reduction in inconsistent ordered decision tables with a single decision attribute. A fictitious numerical example is employed to substantiate the conceptual argument throughout the paper.